Patch Testing With Nickel Sulfate 5.0% Traces Significantly More Contact Allergy Than 2.5%: A Prospective Study Within the International Contact Dermatitis Research Group. Issue 6 (20th November 2022) - Svedman, Cecilia; Ale, Iris; Goh, Chee-Leok; Goncalo, Margarida; Lee, Jun Young; Ljubojevic Hadžavdić, Suzana; Matsunaga, Kayoko; Bach, Rasmus Overgaard; Pratt, Melanie; Puangpet, Pailin; Sasseville, Denis; Andersen, Klaus E.; et al.
Abstract : Background: Nickel allergy is the most common contact allergy, and a nickel salt is, therefore, included in most baseline patch test series. In the baseline series of the International Contact Dermatitis Research Group and the American Contact Dermatitis Society, nickel sulfate hexahydrate (NSH) in petrolatum at 2.5% is included, whereas NSH at 5.0% is included in many other baseline series, such as the European and Swedish ones. Objective: The aim of the study is to investigate whether NSH at 5.0% detects significantly more contact allergy than NSH 2.5% when both preparations are tested simultaneously in consecutive dermatitis patients. Patients and Methods: Two thousand two hundred eighty-seven consecutive dermatitis patients were patch tested simultaneously with NSH in petrolatum at 2.5% and 5.0%. The allergy rates were compared for all clinics individually and combined using McNemar test, 2-sided. Results: Contact allergy to NSH 5.0% and 2.5% was found in 20.3% and 16.8%, respectively ( P < 0.0001). In 6 of 11 clinics, significantly more patients tested positive to the higher NSH concentration. For the 2 clinics in North America combined, significantly more patients tested positive to NSH 5.0%. Conclusions: The NSH preparation in the International Contact Dermatitis Research Group baseline patch test series should be considered to be changed from NSH 2.5% (1 mg NSH/cm 2 ) to 5.0% (2 mg NSH/cm 2 ).